AUDITING ELECTRONIC RECORDS. - Kaufman, Felix; Schmidt, Leo A. (The Accounting Review, 1957)
Abstract Many accountants, both in public and private accounting, have been striving mightily in recent years to see their way through the maze and mists of electronic data processing. To some extent, the highly placed controller or the partner public accountant will be able to dodge the necessity for this new learning by delegating it to the "systems" or department. Controllers discharging this responsibility through their systems departments have the direct responsibility for determining the feasibility of adoption of some electronic data processing layout. Public accountants, if they are rendering management and systems service, face the same problem of adoption and installation with and for their clients. In many respects, the present situation is not unlike that faced by the public accountants twenty-five years ago when punched card accounting techniques were sweeping into the accounting office. For the fully "electronified" areas of the accounting system there will be virtually nothing left of old on-the-scene audit techniques.